Building consumer trust in digital pawnshop services: A systematic review of governance, data security, and user experience (UX) determinants - Shintia Maharani; Anggi Yulistia Maharani (Environmental, Social, Governance and Sustainable Business, 2026)
Background: Digital pawnshops, a novel FinTech service, face a critical adoption barrier: consumer trust. This challenge is magnified by the high-stakes nature of entrusting tangible collateral through a digital interface. This review systematically synthesizes empirical research on the determinants of consumer trust, focusing on governance, data security, and user experience (UX). Methods: Adhering to PRISMA 2020 guidelines, this systematic review searched Scopus and Web of Science for original empirical articles. Methodological quality was appraised using the MMAT, and findings were integrated via thematic synthesis. Findings: The search and screening process yielded 17 original articles meeting the inclusion criteria. The evidence base is characterized by a strong geographical concentration in Southeast Asia and a heavy theoretical reliance on technology acceptance models (TAM/UTAUT). The thematic synthesis identified three core themes, governance frameworks, including perceived regulatory support and consumer protection policies, function as the foundational layer of trust, data security, encompassing perceived security and ethical data handling, was identified as a critical antecedent to trust, user experience (UX), specifically system reliability, platform usability, and transparent interface communication, functions as the primary mediator, translating institutional security and governance into perceived trustworthiness. Conclusion: The review concludes that trust in digital pawnshops is hierarchical: Governance and security provide the foundation, but UX acts as the critical mediator. In this high-stakes context, platform reliability is paramount. Technical or UX failures are not seen as mere inconveniences but as fundamental security breaches that catastrophically erode trust. Novelty/Originality of this article: This review provides the first systematic synthesis for the digital pawnshop niche, addressing a fragmented knowledge base. Its primary novelty is an evidence-based, hierarchical model of trust. This model posits that governance and security are foundational, while UX acts as the tangible interface through which trust is ultimately perceived and validated by the consumer.